2021
DOI: 10.1186/s12871-021-01459-7
|View full text |Cite
|
Sign up to set email alerts
|

Two types of anaesthesia and length of hospital stay in patients undergoing unilateral total knee arthroplasty (TKA): a secondary analysis based on a single-centre retrospective cohort study in Singapore

Abstract: Background Evidence regarding the relationship between the type of anaesthesia and length of hospital stay is controversial. Therefore, the objective of this research was to investigate whether the type of anaesthesia was independently related to the length of hospital stay in patients undergoing unilateral total knee arthroplasty (TKA) after adjusting for other covariates. Methods The present study was a cohort study. A total of 2622 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…This is consistent with the findings of the present study. General anesthesia has been reported to prolong the length of hospital stay in patients undergoing unilateral TKA [ 20 , 21 ]; this is also consistent with our findings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings of the present study. General anesthesia has been reported to prolong the length of hospital stay in patients undergoing unilateral TKA [ 20 , 21 ]; this is also consistent with our findings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although general and local anesthesia, including spinal subarachnoid anesthesia, are suitable for TKA,, local anesthesia has been reported to shorten the length of hospital stay compared to general anesthesia [17][18][19] , which was consistent with the ndings of the present study. General anesthesia has been previously reported to prolong the length of hospital stay in patients undergoing unilateral TKA 20,21 , consistent with our ndings. However, contrastingly, some studies have shown that the method of anesthesia does not affect the length of hospital stay 22 .…”
Section: Related Factors Affecting the Length Of Hospital Staysupporting
confidence: 92%
“…Total Knee Arthroplasty (TKA) is the primary surgical procedure for treating severe knee disorders, relieving knee pain, and reestablishing knee function (1). It can help patients restore knee joint function and improve their quality of life (2).…”
Section: Introductionmentioning
confidence: 99%